Dynamic response of pressure transmission lines to pulse input: technical report - Gorove, Arpad, author; Cermak, J. E. (Jack E.), author; Fluid Dynamics and Diffusion Laboratory, College of Engineering, Colorado State University, publisher (Colorado State University. Libraries, 1967)
The dynamic response of pressure transmission lines to pulse input was investigated experimentally. The most commonly used commercially available flexible Tygon tubings were examined at a constant 1/ 2-psi air pressure with a frequency up to 300 cps. Short tubings, from 1 inch to 3 feet and inside diameters between .052 inch and 1/4 inch, were tested in the experiment. Pressure transducers were selected which had very small internal volume and the reference transducer was kept at a practical minimum distance from the pressure source. Tubing with and without inlet restriction has been investigated to determine the phenomenon of resonant frequency. To determine the effect of the elastic wall of the tubing on the pressure response, comparison measurements were taken in rigid wall, flexible Tygon, and rubber tubings. Phase shift of flexible tubings with various lengths and inside diameters were determined for the frequency range 0-300 cps.
CER66-67AP-JEC51.
June 1967.
U.S. Army Research Grant.
Keywords: Pressure -- Measurement